Improving neonatal health with family-centered, early postnatal care: A quasi-experimental study in India. - Seema Murthy; Shirley Du Yan; Shahed Alam; Amit Kumar; Arjun Rangarajan; Meenal Sawant; Huma Sulaiman; Bhanu Pratap Yadav; Tanmay Singh Pathani; Anand Kumar H G; Sareen Kak; Vinayaka A M; et al. (Public Library of Science (PLoS), 2023)
Despite the global decline, neonatal mortality rates (NMR) remain high in India. Family members are often responsible for the postpartum care of neonates and mothers. Yet, low health literacy and varied beliefs can lead to poor health outcomes. Postpartum education for family caregivers, may improve the adoption of evidence-based neonatal care and health outcomes. The Care Companion Program (CCP) is a hospital-based, pre-discharge health training session where nurses teach key healthy behaviors to mothers and family members, including skills and an opportunity to practice them in the hospital. We conducted a quasi-experimental study to assess the effect of the CCP sessions on mortality outcomes among families seeking care in 28 public tertiary facilities across 4 Indian states. Neonatal mortality outcomes were reported post-discharge, collected via phone surveys at four weeks postpartum, between October 2018 to February 2020. Risk ratios (RR), adjusting for hospital-level clustering, were calculated by comparing mortality rates before and after CCP implementation. A total of 46,428 families participated in the pre-intervention group and 87,305 in the post-intervention group; 76% of families completed the phone survey. Among the 33,599 newborns born before the CCP implementation, there were 1386 deaths (NMR: 41.3 deaths per 1000 live births). After the intervention began, there were 2021 deaths out of 60,078 newborns born (crude NMR: 33.6 deaths per 1000 live births, RR = 0.82, 95% CI: 0.76, 0.87; cluster-adjusted RR = 0.82, 95% CI: 0.71, 0.94). There may be a substantial benefit to family-centered education in the early postnatal period to reduce neonatal mortality.